Evaluation method of oil saturation index OSI for shale oil reservoir based on well logging data - Tian, Han; Wu, Hongliang; Yan, Weilin; Feng, Zhou; Li, Chaoliu; Ren, Li; Xu, Hongjun (Frontiers in Earth Science, 2024)
Oil saturation index (OSI) serves as an important indicator for potential movable hydrocarbons evaluation of shale oil reservoirs, which is mainly obtained through rock pyrolysis experiments. A new method is proposed to evaluate the OSI of shale quantitatively by NMR logging. The OSI value can be accurately obtained through the experimental measurement of organic carbon content (TOC) and rock pyrolysis of shale samples, which can identify the development of mobile hydrocarbons. Subsequently, the mobile fluid porosity can be obtained based on NMR logging. In order to establish the relationship between OSI value and mobile fluid porosity, it is important to determine the T2 cutoff value corresponding to the mobile fluid porosity. Take shale samples from the first member of the Qingshankou Formation (“Qing 1 Member”) as an example, based on 2D NMR experimental analysis in three different states (original, dried state at 105°C, saturated kerosene), the NMR T2 cutoff value of movable fluid porosity in the shale of Qing 1 Member is clarified as 8 ms. Integrating rock pyrolysis and 2D NMR experiments, it suggests that the NMR bin porosity with T2>8 ms has a good linear relationship with the OSI value obtained by pyrolysis analysis. The NMR bin porosity with T2> 8 ms reflects the OSI value of shale effectively. The larger the NMR bin porosity with T2>8 ms, the higher the mobile oil content of shale reservoir, which is consistent with the understanding of oil-bearing large pores in the Gulong Shale. The NMR bin porosity can continuously evaluate the vertical variation of the mobile hydrocarbon content. Compared with the traditional experimental measurement of finite depth points, this method has significant advantages, and can avoid the possibility of missing potentially movable oil layers.